Chemical Analysis of River Water Collected From Different Sites Of Kali Nadi - NIRANJAN LAL; SMT. VANADANA GARG (International Journal of Pharma and Bio Sciences, 2011)
The quality of ground water depends on the ions which are dissolved in ground water. The major ions which are responsible to maintain the quality of ground water are carbonate (CO3–) and bicarbonate (HCO3–), Chloride (Cl-), Sulphate (SO4–), Nitrate (NO3–), Phosphate (PO4—), and Fluoride (F-).The above ions are present in the form of anions. These anions are in general maintain by the cat ions as Cu++, Mg++, Na+, & K+. These cations are present in the form of hardness and salinity. 3 water samples are collected from different locations of kali nadi, District Meerut during summer (2008).The ionic concentrations are expressed in mg/ltr.